Circumcision and the Community - Zaghal, Ahmad; Rahman, Nishat (IntechOpen, 2020)
Male circumcision is one of the oldest and the most common procedures in the world; it is performed for both medical and non-medical reasons. Circumcision is a relatively simple procedure; however, if not done properly, can lead to major complications such as iatrogenic injury of the glans or the urethra. The debate over the advantages of the routine cultural circumcision is still ongoing with a significant dichotomy between the opinions of the experts in the field. The main purpose of this book is to present a discussion on the pros and cons of the non-medical male circumcision from a public health point of view, and to raise awareness about the potential complications of this procedure.